ANALYSIS OF STUDENTS’ NUMERICAL LITERACY BASED ON MATHEMATICAL ANXIETY IN SOLVING TWO-VARIABLE LINEAR EQUATION SYSTEM AT JUNIOR HIGH SCHOOL - Andini, Desi Putri; Hadjar, Ibnu; sukayasa, Sukayasa; M, Bakri (JME (Journal of Mathematics Education), 2025)
This study aims to obtain a description of students' numeracy literacy based on their mathematical anxiety in solving Two-Variable Linear Equation System problems. This study was conducted at Bala Keselamatan Palu Junior High School. The study employed a qualitative approach involving three eighth-grade students selected based on levels of mathematical anxiety (high, moderate, and low).  The research subjects were selected based on the results of a mathematical anxiety questionnaire, taking into account the recommendations of the mathematics teacher. Data were collected through written Two-Variable Linear Equation System problem-solving tests and semi-structured interviews and analyzed using Miles and Huberman’s qualitative data analysis model.  The results indicate that students with low and moderate mathematical anxiety were able to meet all numeracy literacy indicators, although procedural weaknesses were observed in students with moderate anxiety. In contrast, students with high mathematical anxiety were only able to meet one numeracy literacy indicator.